The effect of partial dissolution on sea-ice chemical transport: a combined model–observational study using poly- and perfluoroalkylated substances (PFASs) - M. Thomas; B. Cate; J. Garnett; I. J. Smith; M. Vancoppenolle; C. Halsall (The Cryosphere, 2023)
We investigate the effect of partial dissolution on the transport of chemicals in sea ice. Physically plausible mechanisms are added to a brine convection model that decouples chemicals from convecting brine. The model is evaluated against a recent observational dataset where a suite of qualitatively similar chemicals (poly- and perfluoroalkylated substances, PFASs) with quantitatively different physico-chemical properties were frozen into growing sea ice. With no decoupling the model performs poorly – underestimating the measured concentrations of high-chain-length PFASs. A decoupling scheme where PFASs are decoupled from salinity as a constant fraction of their brine concentration and a scheme where decoupling is proportional to the brine salinity give better performance and bring the model into reasonable agreement with observations. A scheme where the decoupling is proportional to the internal sea-ice surface area performs poorly. All decoupling schemes capture a general enrichment of longer-chained PFASs and can produce concentrations in the uppermost sea-ice layers above that of the underlying water concentration, as observed. Our results show that decoupling from convecting brine can enrich chemical concentrations in growing sea ice and can lead to bulk chemical concentrations greater than that of the liquid from which the sea ice is growing. Brine convection modelling is useful for predicting the dynamics of chemicals with more complex behaviour than sea salt, highlighting the potential of these modelling tools for a range of biogeochemical research areas.